1982
DOI: 10.1136/bmj.285.6346.940
|View full text |Cite
|
Sign up to set email alerts
|

Residual amblyopia in recruits to the British Army.

Abstract: effect; the mechanism of this is unknown but is associated with prolongation of the QT interval.3 There is little doubt that in the two cases reported here amiodarone exerted an antiarrhythmic effect within a few hours of the first oral dose. Possibly previous treatment with other antiarrhythmic agents had in some way sensitised the myocardium to the effects of amiodarone. The prolongation of the QT interval suggests that in our patients oral amiodarone produced an acute pharmacological effect similar to that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

1990
1990
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 1 publication
1
14
1
Order By: Relevance
“…Studies in Scandinavia suggest that the incidence of amblyopia has reduced since the commencement of screening services for children17 but an article looking at the incidence of amblyopia in recruits to the British Army found no convincing change from an incidence of 4.7% males in 1965 to 4-1% in 1976. 18 School visual screening programmes have been criticised because of late referral and the risk this poses to effective treatment for the amblyopia.6 Arguments have been made to remove the school screening service from the system, therefore allowing for reallocation of resources.3 The findings of this study in which preschool screening was found to be inefficient do not support the cessation of school screening. It should be easier to examine all of the children 100 r 90 in a geographical area by screening at school.…”
Section: Discussionmentioning
confidence: 83%
“…Studies in Scandinavia suggest that the incidence of amblyopia has reduced since the commencement of screening services for children17 but an article looking at the incidence of amblyopia in recruits to the British Army found no convincing change from an incidence of 4.7% males in 1965 to 4-1% in 1976. 18 School visual screening programmes have been criticised because of late referral and the risk this poses to effective treatment for the amblyopia.6 Arguments have been made to remove the school screening service from the system, therefore allowing for reallocation of resources.3 The findings of this study in which preschool screening was found to be inefficient do not support the cessation of school screening. It should be easier to examine all of the children 100 r 90 in a geographical area by screening at school.…”
Section: Discussionmentioning
confidence: 83%
“…[11][12][13][14][15][16][17] This chapter summarises the data relating to the prevalence of amblyopia, strabismus and refractive error. Four papers were identified relating to prevalence of amblyopia, [11][12][13][14] three papers reporting the prevalence of strabismus [15][16][17] and one paper reporting the prevalence of refractive errors. 17 It can be seen that the literature searches elicited few data regarding the prevalence or incidence of amblyopia, strabismus and refractive error.…”
Section: Results Of the Systematic Reviewmentioning
confidence: 99%
“…Hopkisson and colleagues 12 reported on the prevalence of amblyopia in British Army recruits, and examined whether prevalence has altered since the introduction of screening programmes. The authors selected a 20% random sample of recruits' medical records for two years (1965 and 1976) and examined the number of recruits with amblyopia (defined as a difference between the two eyes of two or more lines on the Snellen acuity chart, with the good eye having vision of 6/9 or better).…”
Section: Prevalence Of Amblyopiamentioning
confidence: 99%
“…It has been reported that 75% of orthoptic departments in the UK provide such a service2 but despite this there is no evidence for a reduction in the prevalence of amblyopia in adults and one study found that the prevalence in army recruits had remained the same over a 10 year period from 1965 to 1976 3. Factors which could limit the success of such programmes might include (1) inability of the screening programme to reach the affected population; (2) poor detection and treatment of amblyopia; (3) difficulty retaining patients in treatment programmes; or (4) post-treatment deterioration in visual acuity in the amblyopic eye.…”
mentioning
confidence: 99%